BEYOND THE PROMOTION OF ECONOMIC COOPERATION: THE ECONOMIC COMMUNITY OF WEST AFRICAN STATES PEACEKEEPING INVOLVEMENTS IN WEST AFRICA - ugo chuks okolie; Ejogba Abraham ORHERO (GLOBAL INSIGHT JOURNAL, 2023)
In order to raise the living standards of its people, maintain and improve economic stability, foster relations among Member States, and contribute to the advancement and development of the African continent, Economic Community of West African States (ECOWAS) was established. Its goal is to promote cooperation and integration that will result in the creation of an economic union in West Africa. According to a set of guiding principles, such as impartiality, the parties' consent, and the non-use of force unless necessary for self-defense, a third party intervention known as "peacekeeping" is conducted. The study examines the role played by ECOWAS in preserving stability and peace on the African continent, focusing in particular on the ECOMOG intervention in Liberia, Sierra Leone, and Guinea Bissau. The regional security complex theory was accepted. The research was qualitative, and its historical analysis heavily drew on secondary sources.  The essence of the resolutions of the UN Security Council and the ECOWAS Mediation and Security Council, and consequently the legal foundation for peacekeeping and peace enforcement are contained in peace agreements. As a result, peace agreements are essential to the management and resolution of conflicts. However, it is erroneous to assume that the heads of armed factions are sane political actors motivated by genuine grievances and that they will thereby agree to mediated agreements. The offering of carrots (the confidence-building approach) must therefore be combined with strong diplomacy supported by a credible enforcement capacity in order for peace to be successfully implemented in the West African region.  The study recommends, among other things, that the framework for the ECOWAS legal system governing peace and security should be the member states. This is because the majority of democracies in the sub-region elect postcolonial states with a predominance of coloniality of power disguising itself as democracy and causing conflicts in the majority of countries within the West African security complex, ECOWAS must exert pressure on its member states to step up their efforts to improve democracy in their respective countries.